Effects of Metabolic Syndrome and Its Components on the Prognosis of Endometrial Cancer - Yang, Xiao; Li, Xingchen; Dong, Yangyang; Fan, Yuan; Cheng, Yuan; Zhai, Lirong; Zhang, Shuyi; Zhou, Jingyi; Wang, Jianliu (Frontiers in Endocrinology, 2021)
Objective To explore the effects of metabolic syndrome (MetS) and its components on the prognosis of endometrial cancer (EC) and to identify the key component of MetS associated with EC. Methods 506 patients who were surgically confirmed to have EC at the Department of Obstetrics and Gynecology, People’s Hospital of Peking University, between 2010 and 2016 were analyzed. The follow-up time was cut off at December 2019. We defined MetS according to the Chinese Diabetes Society standard in 2004. Results Among the 506 EC patients, there were 153 patients with MetS and 388 without MetS at diagnosis according to the definition of MetS. Patients with MetS had more elder and postmenopausal proportion, and MetS was closely positive related to tumor grade, stage, LNM, LVSI and MI. The univariate analysis showed that MetS was closely related to OS (HR=2.14; P=0.032) and RFS (HR=1.80; P=0.045) of EC patients. The K-M analysis also indicated that EC patients with MetS had shorter OS and RFS than that without MetS, and patients with ≥3 components had worse outcome than 1-2 components and 0 components (P<0.05). In the multivariate-adjust model, after adjusting for age, histotype, tumor grade and stage, HDL-C was associated with a increased risk of EC death (HR=2.2, P=0.034), while MetS showed to be not statistically significant correlation. ROC analysis found that the area under curve (AUC) of combine (HDL-C+grade+stage) factor was better than traditional stage or grade at 1-,3- and 5-year survival, then a nomogram based on HDL-C, grade and stage was constructed to predict survival of EC patients. The calibration curve analysis and decision curve analysis (DCA) showed the nomogram we constructed could better predict the survival of patients with EC. Conclusion MetS was closely related to poor prognosis in patients with EC. The prevalence of the individual components of MetS increases with worse outcome of EC patients. A nomogram based on HDL-C, grade and stage has good ability to predict survival of EC patients.